Competition over collective victimhood recognition: When perceived lack of recognition for past victimization is associated with negative attitudes towards another victimized group. (7th June 2017) - De Guissmé, Laura; Licata, Laurent
Abstract: Groups that perceive themselves as victims can engage in "competitive victimhood." We propose that, in some societal circumstances, this competition bears on the recognition of past sufferings—rather than on their relative severity—fostering negative intergroup attitudes. Three studies are presented. Study 1, a survey among Sub‐Saharan African immigrants in Belgium ( N  = 127), showed that a sense of collective victimhood was associated with more secondary anti‐Semitism. This effect was mediated by a sense of lack of victimhood recognition, then by the belief that this lack of recognition was due to that of Jews' victimhood, but not by competition over the severity of the sufferings. Study 2 replicated this mediation model among Muslim immigrants ( N  = 125). Study 3 experimentally demonstrated the negative effect of the unequal recognition of groups' victimhood on intergroup attitudes in a fictional situation involving psychology students ( N  = 183). Overall, these studies provide evidence that struggle for victimhood recognition can foster intergroup conflict.